2012
DOI: 10.1007/s00125-012-2472-x
|View full text |Cite
|
Sign up to set email alerts
|

Age-related islet autoantibody incidence in offspring of patients with type 1 diabetes

Abstract: Aims/hypothesis Seroconversion to islet autoantibodies precedes type 1 diabetes. This study aimed to identify periods of high seroconversion incidence, which could be targeted for mechanistic and therapeutic studies. Methods Incidence of islet autoantibodies was calculated in 1,650 genetically at-risk children followed with measurements of islet autoantibodies and thyroid autoantibodies at age 9 months and 2, 5, 8, 11, 14 and 17 years. Peak incidence periods were confirmed in a second cohort of 150 children fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
183
3
18

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(218 citation statements)
references
References 28 publications
14
183
3
18
Order By: Relevance
“…These findings suggest that susceptibility to autoimmunity against specific beta cell autoantigens occurs at distinct age periods. This study extends previous work from our own BABYDIAB study [3], the Finnish Type 1 Diabetes Prediction and Prevention (DIPP) study [14] and The Environmental Determinants of Diabetes in the Young (TEDDY) study [15]. It involved substantial follow-up of the cohort and uniquely characterised the islet autoantibodies at seroconversion and follow-up.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…These findings suggest that susceptibility to autoimmunity against specific beta cell autoantigens occurs at distinct age periods. This study extends previous work from our own BABYDIAB study [3], the Finnish Type 1 Diabetes Prediction and Prevention (DIPP) study [14] and The Environmental Determinants of Diabetes in the Young (TEDDY) study [15]. It involved substantial follow-up of the cohort and uniquely characterised the islet autoantibodies at seroconversion and follow-up.…”
Section: Discussionsupporting
confidence: 55%
“…In accordance with the visit schedule, antibody incidence (per 1,000 person-years) was calculated from samples obtained within the age intervals 0-18 months (mean age of sample group, 0.85 years), 18-42 months (mean age of sample group, 2.0 years), 42-78 months (mean age of sample group, 5.0 years), 78-114 months (mean age of sample group, 8.0 years), 114-150 months (mean age of sample group, 11.0 years), 150-186 months (mean age of sample group, 14.0 years) and 186-204 months (mean age of sample group, 17.0 years), by dividing the number of children who had newly seroconverted to islet autoantibody positivity by the number of children followed at each interval [3]. SE calculations were based on the Cooper-Pearson methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, many multiple islet autoantibody-positive children are likely to have transitioned from single to multiple islet autoantibodies. We [2,3], and others [4] have reported that multiple islet autoantibody-positive children frequently seroconvert in the first 2 years of life, but little is known of the timing of transition from single to multiple islet autoantibody positivity. This knowledge is important for the design of screening and re-screening strategies.…”
mentioning
confidence: 89%
“…This knowledge is important for the design of screening and re-screening strategies. Here we analysed the prospectively followed German BABYDIAB/BABYDIET birth cohort [2,5] to address this.…”
mentioning
confidence: 99%